PERAN ASISTEN STORE MANAGER DALAM PENERAPAN MANAJEMEN OPERASIONAL DI GERAI CHATIME JABABEKA CIKARANG - Zulkifli Zulkifli; Fakhruddin Kurnia M (Paser Institute Management and Busines, 2025)
This study investigates the role of the Assistant Store Manager in implementing operational management at the Chatime Jababeka Cikarang outlet. The background of this research is based on the fact that middle level leadership is very important to ensure that daily operations in ready-to-drink beverage retail run well and smoothly. Assistant Store Manager (ASM) is a strategic role that manages operational implementation in the field with central management policies. To explain the function of ASM in managing resources, monitoring employee performance, implementing standard operating procedures, and handling customers, this research uses qualitative methodology, as well as field observations. Research shows that ASM improves team efficiency, maintains operational stability, and helps achieve store sales targets. Additionally, good communication, management skills, and use of technology are critical to success in the role. So, ASM is very important for operational technical matters and forming work culture and maintaining competitive outlets in the midst of increasingly fierce industrial competition.